Species and Functional Dynamics of the Demersal Fish Community and Responses to Disturbances in the Pearl River Estuary - Zeng, Zeyu; Cheung, William W. L.; Lai, Han; Yi, Huadong; Bi, Sheng; Li, Haiyang; Chen, Xiaoli; Su, Yuqin; Liu, Xuange; Chen, Qiuxian; Zhang, Zhilun; Wei, Xuchong; et al. (Frontiers in Marine Science, 2022)
Fishery resources are threatened by environmental changes and anthropogenic pressures, particularly in coastal ecosystems. It is crucial to understand the changes of fish communities and their responses to environmental changes and human disturbances to formulate rational fisheries and ecosystem-based management. The Pearl River Estuary (PRE) is a typical sub-tropic coastal ecosystem located in the center of the Guangdong-Hong Kong-Macao Greater Bay Area in the northern South China Sea. The demersal fish in the PRE is traditionally targeted as commercial fishing and severely impacted by overexploitation and hypoxia in the last few decades. In this study, we analyze the fish survey data during the period of 2020~2021 using multivariate statistics to investigate the impacts of human disturbances on the species and functional dynamics of the demersal fish community in the PRE. The results reveal that dissolved oxygen and temperature have significant correlations with the functional traits of the demersal fish community. The impacts of hypoxia on the demersal fish vary with species and locations. We found that the mean functional redundancy of the demersal fish community in the PRE was high across three surveys, but the functional diversity was low in this region. The abundance and richness of the demersal fish community increased during the summer fishing moratorium in the South China Sea in 2021, but the functional diversity did not increase significantly. We conclude that the high functional redundancy in the PRE might not be sufficient to buffer against environmental disturbances because of its low functional diversity. Our study highlights the complicated interactions between the demersal fish community and disturbances in the PRE. Understanding the traits structure and functional diversity of the fish community can help elucidate the factors determining the dynamic responses of the fish community to disturbances.